OPERATIONAL SURGERY AND TOPOGRAPHIC ANATOMY: CLINICAL SIGNIFICANCE AND RESEARCH PERSPECTIVES - Suyunova Zamira Axatovna; Awaish Asim (TADQIQOTLAR, 2025)
Abstract Operational surgery and topographic anatomy represent fundamental disciplines in medical education and clinical practice. Their integration provides essential knowledge for safe and effective surgical interventions. This study analyzes the role of topographic anatomy in surgical operations, evaluates teaching methods, and highlights its importance in minimizing intraoperative complications.